The Influence of Bureaucracy Apparatus' Behaviour to Service Quality of Land Certificate (Study at the Land Office of Majalengka, West Java) - Aceng Jarkasih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to show the bureaucratic apparatus's behavior towards the quality of land certificate services and find new concepts about the bureaucratic apparatus's behavior. The methodology used in this research is the explanatory survey method, following the study's objectives, which will explain the relationship between variables, namely the behavior of bureaucratic officials to the quality of land certificate services. Based on the results of research and discussion of the influence of the behavior of bureaucratic officials on the quality of service certificates at the Land Office of Majalengka Regency, the following can be disclosed: 1) The behavior of bureaucratic officials is oriented towards the dimensions of justice, empathy, discipline, sensitivity, and responsibility. Significantly affects the quality of land certificate services; 2) The height bureaucratic behavior towards the quality of land certificate services is determined by the dimensions of Fairness, empathy, discipline, sensitivity, and responsibility. and 3) Furthermore, from the results of this research, it can be found and developed a new model that "Kharimah behavior" are words for the dimension of caring in providing public services.